Vertical Transmission in Pregnancy with COVID-19 For the January-April 2021 Period at the Prof. dr. I.G.N.G. Ngoerah General Hospital, Denpasar, Indonesia - Anak Agung Gede Putra Wiradnyana; Ida Bagus Putra Adnyana; Kadek Fajar Marta; Anak Agung Gede Marvy Khrisna Pranamartha (European Medical Journal, 2023)
Background: COVID-19 is an infectious disease that can infect anyone, including pregnant females, a population that is susceptible to various infections. This has become a challenge because of the risk of vertical transmission and increased foeto-maternal mortality. That authors' purpose was to present the incidence of pregnancy with COVID-19 and the vertical transmission in pregnancies with COVID-19. Methods: This study used cross-sectional observational research and was carried out at the Prof. dr. I.G.N.G. Ngoerah Denpasar General Hospital, Denpasar, Indonesia, from January-April 2021. The authors used primary data from pregnant females who presented at the hospital with positive severe acute respiratory syndrome coronavirus 2 PCR results. Additional instruments included data collection forms and medical records. Results: Based on primary data, a total of 15 pregnant females with COVID-19 were identified from a total of 165 deliveries in that period. The prevalence of COVID-19 events in pregnant females was 9.09%. It was found that the rapid blood antibody results for all infants had non-reactive results for IgM. It can be assessed that the relative risk of transmitting COVID-19 antibodies from mother to foetus is three times (risk ratio: 3.00; 95% confidence interval: 1.56-64.26). One baby was found with reactive examination results so that the prevalence ratio obtained was 11.7 (prevalence ratio: 11.7; 95% confidence interval: 1.63-35.57). Conclusion: The prevalence rate of pregnant females with COVID-19 at the Prof. dr. I.G.N.G. Ngoerah General Hospital for the period of January-April 2021 was 9.09%. COVID-19 infection in pregnancy can increase the risk of vertical transmission of COVID-19 by 11.7 times compared with pregnancy without COVID-19 infection.